DEVELOPING E-LEARNING BY USING KELASE IN BIOLOGY SUBJECT FOR XI GRADE IN SMA NEGERI 1 SEMARAPURA - Dewi, Leoni (Journal of Education Reseach and Evaluation, 2017)
The problem found at SMA Negeri 1 Semarapura was that the learning achievement in Biology was not yet satisfactory. This study was aimed at (1) describing the design of E-learning development, (2) describing the E-learning design quality validation result according to the expert judges and the product try out result, (3) finding out the effectiveness of E-learning developed. This study was research and development. It used Hannafin and Peckâs model. The data which were collected in this study were qualitative and quantitative data. The data were collected through document recording, questionnaire and test. The results were as follows, (1) the E-learning design for Biology subject using Hannafin and Peckâs model which covered three stages, (2) the E-learning for Biology subject that was developed was valid; (a) the result of content expertsâ judgment about the content of the subject shows that the E-learning falls into very good qualification (91.4%), (b) the result of the E-learning expertsâ judgment of the E-learning design shows that E-learning falls into good qualification (90.06%), (c) the result of instructional design expertsâ judgment about the E-learning falls into good qualification (89.02%), (d) the result of individual try out, small group try out, and field try out show that E-learning falls into good qualification (89.93%), (89.34%), and (83.03%), (3) the effectiveness of the development shows that E-learning that was developed was effective in enhancing Biology learning achievement (tobs. = 25.89 > tc.v. = 2.390, at the 5% level of significance). That means that E-learning has proven to be effective in enhancing Biology learning achievement significantly.